Evaluating emotion processing and trait anxiety as predictors of non-criminal psychopathy. (July 2015) - Burns, Sarah; Roberts, Lynne D.; Egan, Sarah; Kane, Robert
Highlights: Anxiety and emotion processing were investigated as predictors of psychopathy subtypes. Emotion regulation deficits and anxiety were strong predictors of secondary psychopathy. Emotion manipulation was a strong predictor of primary and secondary psychopathy. Results illustrate the importance of further investigation of non-criminal psychopathy. Abstract: This study's primary aim was to investigate if trait anxiety and other emotion processing variables would be additive predictors that will differentially predict primary and secondary psychopathy, as previous research has yet to examine the relative contributions of these constructs in a non-criminal population. A convenience community sample ( N  = 470) was obtained using an online survey. Structural equation modelling analyses demonstrated that trait anxiety, reappraisal and emotional manipulation are significant predictors of primary psychopathy. Trait anxiety, emotion manipulation, poor emotional skills and general emotion dys-regulation were found to be significant predictors of secondary psychopathy. From these findings, particularly noteworthy relationships are those between trait anxiety and secondary psychopathy (16% of the variance), and emotion manipulation and primary psychopathy (17.64% of the variance). In addition, there was preliminary evidence that emotion processing variables may partially mediate the relationship between trait anxiety and psychopathy subtypes. These findings have important implications, including the relevance of the findings to psychopathy conceptualised as a personality trait and the applicability of the findings in different non-forensic settings.